A simulated emergency department for medical students. (17th July 2016) - Johnson, Patricia; Brazil, Victoria; Raymond‐Dufresne, Éliane; Nielson, Tracy
Summary: Background: During their training, medical students often undertake a rotation in an emergency department (ED), where they are exposed to a wide variety of patient presentations. Simulation can be an effective teaching strategy to help prepare learners for the realities of the clinical environment. Simulating an ED shift can provide students with the opportunity to perform a range of clinical activities, within their scope of practice, in a supervised and supportive learning environment. Medical students often undertake a rotation in an emergency department Context: There is limited literature describing the structure, syllabus, feasibility and perceived usefulness of simulating a typical ED for medical student training. Innovation: We developed a simulated ED (simED) teaching session for medical students at our university. Students were informed of the purpose and learning tasks of the session prior to attendance. At the start of their 2‐hour simED shift students were allocated 'patients' by the Triage nurse. At the completion of their shift, students attended a debriefing discussion. Student feedback indicated that they felt that the simED: provided a good opportunity to practise skills and apply theory to practice; was realistic and challenging; highlighted the importance of teamwork; and enabled them to identify skills requiring further practise. Suggestions for improvements included a longer time spent in the simED and the opportunity to see more patients. Implication: The simED approach seemed to be well received and perceived by medical students as useful preparation for the ED. An overview of the structure, materials and resources used is provided to assist educators seeking to implement similar ED clinical scenarios in their curriculum.